Դերանվանական իրողություններ Մուշ- Տիգրանակերտի բարբառախմբում - Բառնասյան, Ջեմմա (ԳԱԱ ԼԻ հրատ․)
В работе рассмотрены местоимения юго-центральной или Муш- Тигранакертской группы диалектов Западной группировки с учетом своеобразия форм. Результат исследования вновь подтверждает мнение выдающегося диалектолога А.Гарибяна о том, что очень часто местоимения являются показателем, позволяющим установить соседство диалектов. In the paper studied the pronouns south-central or Mush-Tigranakert dialect group of Western grouping taking into account the singularity of forms. The result of the study again confirms the opinion of famous dialectologist A.Gharibyan that very often the pronouns are the indication of clarifying the circumstance of dialects being neighbors to each other.
Keywords: Հայոց լեզու; Լեզվաբանություն